Concerns about covert HIV testing are associated with delayed presentation in Ethiopian adults with suspected malaria: a cross-sectional study. (December 2015) - Tadesse, Frew; Deressa, Wakgari; Fogarty, Andrew
Abstract Background Although early diagnosis and prompt treatment is important in preventing mortality from malaria, presentation of symptomatic individuals is often relatively late. One possible contributing factor is that fear of covert human immunodeficiency virus (HIV) testing delays presentation in adults. We aimed to survey the magnitude of such concerns and their association with delayed presentation with suspected malaria. Methods The study design was a health facility-based cross-sectional survey. The study population consisted of adults with suspected malaria who presented to health centres in central Ethiopia. Data were collected on attitudes to HIV testing and the duration between onset of symptoms and treatment seeking for suspected malaria. Results Eight hundred and ten individuals provided data. Of these, 406 (50 %) perceived that HIV testing was routinely done on blood donated for malaria diagnosis, and 327 (40 %) considered that community members delayed seeking medical advice because of these concerns. Concerns about HIV testing were associated with delays in attending for malaria diagnosis and treatment, with 117 individuals (29 %) of those with concerns about covert HIV testing waiting for 4 days or more, compared to 89 (22 %) of those who did not have any such concerns (p  = 0.03). One hundred and twenty nine (16 %) individuals stated that concern about HIV testing was the main reason for the delay in seeking treatment, and 46 % of these individuals presented after experiencing symptoms of malaria infection for three days or more compared to 22 % of the 681 individuals who had no such concerns (p  < 0.001). Analysis stratified by health centre demonstrated that these associations were a consequence of Meki health centre (odds ratio for duration of symptoms greater than 3 days if patient has concerns about HIV testing was 8.72; 95 % confidence intervals 3.63 to 20.97). Conclusions In adults living in central Ethiopia, the perception that HIV testing accompanied the investigation of suspected malaria was common. This is likely to impede presentation for early medical treatment in some areas and represents a reversible risk factor that deserves further study.